Oral Self-examination: An Approach for Early Recognition of Oral Cancer Among Factory Workers: An Experimental Study - Ellappunkal Binoy Ittyavira; Binu Babu (International Journal of Oncological Nursing and Practices, 2023)
Background: Cancer is a worldwide concern and ranks among the most dreaded illnesses across the globe. Oral cancers are one common cancer among all cancers. Objectives: To measure the existing knowledge concerning oral self-examination for timely recognition of oral cancer among factory workers and to develop and administer a planned health education programme of oral self-examination for early recognition of oral cancer among factory workers. 40 factory workers were selected from different factories. Materials and methods: The study employed a one-group pretest-post-test quasi-experimental design. A planned education programme was developed and implemented on the factory workers. Results: In the post-test after the planned health education programme, there was no sample in the poor knowledge group, 22 samples (55%) belong to the average knowledge group. And 18 samples (45%) got promoted to a good knowledge group. The knowledge score increased from 9.95 in the pretest to 19.8 in the post-test. The ‘t’ test value is 21.445 and the p-value is 0.000 (<0.05), therefore, the planned health education programme was significantly effective in improving the knowledge of factory workers regarding oral self-examination for early recognition of mouth cancer. With a p-value below 0.05, the null hypothesis is rejected with a confidence level of 95.0%. Conclusion: The results of this study point out that the improved knowledge regarding oral self-examination will help the individual to identify oral cancer. Early recognition of cancer will help to increase survival and also reduces the struggles related to cancer.
Keywords: Oral Cancer; chemotherapy; oral self-examination; planned health education programme